SÍNTESIS DE LA DEFENSA DE LA LIBRE COMPETENCIA EN EL PERÚ: CONTENIDO Y APLICACIÓN DEL DECRETO LEGISLATIVO N° 1034.- LEY DE REPRESIÓN DE CONDUCTAS ANTICOMPETITIVAS (LRCA) - Stucchi, Pierino; Ballón, Fernando (Revista de Derecho, 2019)
The purpose of this article is to analyze the main aspects of the provisions of Legislative Decree No. 1034 - Law on the Repression of Anti-Competitive Conducts and the recent amendments introduced by Legislative Decree No. 1205. The substantive aspects are outlined, such as the scope of the subjective application, the territorial scope, the prohibited conducts and the legal consequences. The procedural aspects are also pointed out, mainly, the procedural instruments with which the competition agency has to ensure effective competition in the market, as well as the possibilities allowed by the termination commitment, the leniency program and the procedure of exoneration from sanction, as well as corrective measures in its two modalities.